2012
DOI: 10.1089/gtmb.2011.0283
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of the CFTR Gene in 225 Children: Identification of Five Novel Severe and Seven Reported Severe Mutations

Abstract: The protocol for identification of mutations in cases of CF in developing countries would have to include a different set of mutations than those reported from western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Recent years have seen publication of genetic and mutation profiles for large case series of osteogenesis imperfecta, skeletal dysplasias, and lysosomal storage disorders. These studies have revealed the unique molecular profile of patients from the India with identification of many novel mutations not previously reported in other populations (Gorospe et al 2004;Pathak et al 2010;Sachdeva et al 2011Sachdeva et al , 2012Shukla et al 2011;Bashyam et al 2012;Dalal et al 2012;Mistri et al 2012;Bidchol et al 2014;Ankala et al 2015;Stephen et al 2015; A. Uttarilli, P. Ranganath, S.J.M. Nurul Jain, K.P.…”
Section: Academic Programs In Medical Geneticsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent years have seen publication of genetic and mutation profiles for large case series of osteogenesis imperfecta, skeletal dysplasias, and lysosomal storage disorders. These studies have revealed the unique molecular profile of patients from the India with identification of many novel mutations not previously reported in other populations (Gorospe et al 2004;Pathak et al 2010;Sachdeva et al 2011Sachdeva et al , 2012Shukla et al 2011;Bashyam et al 2012;Dalal et al 2012;Mistri et al 2012;Bidchol et al 2014;Ankala et al 2015;Stephen et al 2015; A. Uttarilli, P. Ranganath, S.J.M. Nurul Jain, K.P.…”
Section: Academic Programs In Medical Geneticsmentioning
confidence: 93%
“…Use of SNP microarray to identify regions of homozygosity and candidate genes in these regions is a strategy which can be successfully used in the consanguineous families (Stephen et al 2015). Some conditions found to be relatively common have been Van Der Knaap disease with a founder mutation in the Agarwal community from north western India, calpainopahy, recessive forms of Osteogenesis imperfecta, Progressive pseudorheumatoid arthropthy of childhood and Handigodu disease from a specific community in South India (Gorospe et al 2004;Pathak et al 2010;Sachdeva et al 2011Sachdeva et al , 2012Shukla et al 2011;Bashyam et al 2012;Dalal et al 2012;Bidchol et al 2014;Ankala et al 2015). However, the available data on monogenic malformation syndromes and metabolic disorders from India though extensive, represents only tip of the iceberg as a large population still does not have access to the clinical genetics services due to cost and limited number of genetic centers.…”
Section: Spectrum Of Genetic Disordersmentioning
confidence: 99%
“…This suggests the lack of founder or common mutations in CFTR gene and thus emphasises the need for sequencing of all coding regions of the CFTR gene in suspected cases in the Indian population. In the present study except for p.Phe508del no other pathogenic variant was present in the ACMG panel of cystic brosis [59]. In view of the heterogeneity in pathogenic variants, Mandal et al also suggested that a single panel of pathogenic variants cannot be used for diagnosis or carrier testing of CF in India [28].…”
Section: Cftr (Cystic Brosis Transmembrane Conductance Regulator) Patmentioning
confidence: 59%
“…However, it is not predominant mutation in Asian CF patients. Studies from Indian CF patients found low frequency (19-31.1 %,) of del F 508 mutation [9,10]. Another mutation, G551D(or Gly551Asp or Celtic mutation), arises as a consequence of substitution of aspartate residue for a glycine residue at position 551 and accounts for 4 to 5% of alleles [8].…”
Section: Understanding Pathophysiologymentioning
confidence: 99%